2015
DOI: 10.1007/s00261-015-0524-7
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic neuroendocrine tumors: correlation between histogram analysis of apparent diffusion coefficient maps and tumor grade

Abstract: Purpose: To explore the role of histogram analysis of apparent diffusion coefficient (ADC) MRI maps based on entire tumor volume data in determining pancreatic neuroendocrine tumor (PNT) grade. Methods and Materials: Retrospective evaluation of 22 patients with PNTs included low-grade (G1; n = 15), intermediate-grade (G2; n = 4), and high-grade (G3; n = 3) tumors. Regions of interest containing the lesion were drawn on every section of the ADC map containing the tumor and summated to obtain histograms for enti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
43
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 22 publications
4
43
0
1
Order By: Relevance
“…Gallotti et al 17 found that size, presence of pancreatic duct dilatation, and vascular invasion were correlated with high-grade incidentally detected pNETs. Pereira et al 18 and Kim et al 14 reported a correlation between low ADC values and aggressive pNET biology. Similar to our findings, the latter study also demonstrated a correlation between the qualitative assessment of DWI and aggressive tumors.…”
Section: Discussionmentioning
confidence: 96%
“…Gallotti et al 17 found that size, presence of pancreatic duct dilatation, and vascular invasion were correlated with high-grade incidentally detected pNETs. Pereira et al 18 and Kim et al 14 reported a correlation between low ADC values and aggressive pNET biology. Similar to our findings, the latter study also demonstrated a correlation between the qualitative assessment of DWI and aggressive tumors.…”
Section: Discussionmentioning
confidence: 96%
“…[26] Various studies have found that kurtosis of ADC histograms has implications in evaluating cell differentiation and heterogeneity of measured lesions. [2731] With respect to cell heterogeneity, Guan et al [27] found that the normal cervix displays significantly lower ADC kurtosis than cervical cancer because of the homogeneity of normal tissues. Shindo et.…”
Section: Discussionmentioning
confidence: 99%
“…We assume from such findings that the higher ADC kurtosis of TNBC could imply that it has heterogeneous internal components. As for cell differentiation, higher kurtosis is associated with higher stage bladder cancer [28], poorly differentiated gastric carcinomas [29], and higher grade pancreatic neuroendocrine tumors [31] compared to their well-differentiated counterparts. Therefore, higher ADC kurtosis of TNBC is consistent with poorer cell differentiation, reflecting a more aggressive disease course.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we identified the role of the ADC value in the preoperative estimation of recurrence of PNETs at the same time. Several efforts have been made to identify the relationship between diffusion‐weighted imaging and pathologic features or WHO classification . Recent studies have reported that ADC values could be useful for differentiating the malignancy of PNETs and are related to the high grading of PNETs, likely partly explaining the association between ADC values and recurrence .…”
Section: Discussionmentioning
confidence: 64%
“…Several efforts have been made to identify the relationship between diffusion-weighted imaging and pathologic features or WHO classification. 22,23 Recent studies have reported that ADC values could be useful for differentiating the malignancy of PNETs and are related to the high grading of PNETs, likely partly explaining the association between ADC values and recurrence. 24 By contrast, Kim et al 25 reported that the ADC value did not assess RFS after curative FIGURE 4: The nomogram was developed in our cohort incorporating three MRI features.…”
Section: Discussionmentioning
confidence: 99%